2017
DOI: 10.1016/j.jneuroim.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Defining nervous system susceptibility during acute and latent herpes simplex virus-1 infection

Abstract: Herpes simplex viruses are neurotropic human pathogens that infect and establish latency in peripheral sensory neurons of the host. Herpes Simplex Virus-1 (HSV-1) readily infects the facial mucosa that can result in the establishment of a latent infection in the sensory neurons of the trigeminal ganglia (TG). From latency, HSV-1 can reactivate and cause peripheral pathology following anterograde trafficking from sensory neurons. Under rare circumstances, HSV-1 can migrate into the central nervous system (CNS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 87 publications
0
33
0
Order By: Relevance
“…), and from NI littermate controls (n = 3 per group, age and sex matched). (Figure legend continues) through the OB, as the mechanism of viral entry to the CNS (51,52). HSV-1 virus titer was especially high in the TG and BSC of moribund Rel C307X mice.…”
Section: Discussionmentioning
confidence: 99%
“…), and from NI littermate controls (n = 3 per group, age and sex matched). (Figure legend continues) through the OB, as the mechanism of viral entry to the CNS (51,52). HSV-1 virus titer was especially high in the TG and BSC of moribund Rel C307X mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Herpes simplex virus-1 (HSV-1), a DNA virus, has a high seroprevalence in the human population [ 32 ]. When infecting the central nervous system, HSV-1 causes herpes simplex encephalitis, the leading cause of viral encephalitis [ 33 ]. The initial study found that STING deficient mice were extremely susceptible to intravenous infection of HSV-1 [ 34 ].…”
Section: Tmem173 Alleles In Human Healthmentioning
confidence: 99%
“…Using a modified ex vivo tissue explant reactivation assay (i.e., the dissociation method instead of the classical mincing method), Chen et al achieved efficient recovery from the brain stem, olfactory bulb, and frontal cortex but not from the hippocampus, demonstrating that CNS can be a site of latency for HSV-1 ( 26 ). Recent studies have provided evidence that HSV-1 can establish latency in CNS neurons ( 17 , 27 ā€“ 29 ). However, it is uncertain whether neurons constitute the only reservoir of latent HSV-1 in the CNS.…”
Section: Discussionmentioning
confidence: 99%